Remote activation by green-light irradiation of shape memory epoxies containing gold nanoparticles - Leonardi, Agustina Belen (2015)
Shape memory epoxies (SMEs) that can be remotely activated by the use of green light, are described. An epoxy matrix based on on diglycidylether of bisphenol A (DGEBA cured with a mixture of n-dodecylamine (DA) and m-xylylenediamine (MXDA), exhibits excellent shape memory properties as described in a previous paper (Leonardi et al., 2011). Au NPs with an average diameter close to 5 nm could be uniformly dispersed in this matrix using poly(ethylene oxide) (PEO) chains as stabilizer. These NPs showed a significant photothermal effect even at very low concentrations (0.01 wt% as metallic gold), when irradiated with a 532 nm laser at a power close to 2 W/cm2. Under these conditions, a bended bar (1.4-mm thickness) recovered its initial shape in a few seconds. This formulation may be used to build up devices with the necessary mechanical strength and with the possibility to produce shape recovery by remote activation using green light. A second example was analyzed employing an amphiphilic epoxy matrix to produce a uniform dispersion of Au NPs stabilized with dodecyl chains (average diameter close to 3 nm). A bar (1.4-mm thickness) of the SME with 0.04 wt% Au NPs (as metallic gold) showed a fast recovery of its initial shape by irradiation with a 532 nm laser at a power close to 2 W/cm2. This example shows the feasibility of adapting the epoxy chemistry to disperse Au NPs stabilized with different ligands and obtained through robust synthetic methods.